Remote freedoms : politics, personhood and human rights in Aboriginal central Australia - Holcombe, Sarah E. (Sarah Elizabeth), 1967- (Stanford studies in human rights., 2018)
What does it mean to be a 'rights-holder' and how does it come about? Remote Freedoms explores the contradictions and tensions of localized human rights work in very remote Indigenous communities. Based on field research with Anangu of Central Australia, this book investigates how universal human rights are understood, practiced, negotiated, and challenged in concert and in conflict with Indigenous rights. Moving between communities, government, regional NGOs, and international UN forums, Sarah E. Holcombe addresses how the notion of rights plays out within the distinctive and ambivalent sociopolitical context of Australia, and focusing specifically on Indigenous women and their experiences of violence. Can the secular modern rights-bearer accommodate the ideals of the relational, spiritual Anangu person? Engaging in a translation of the Universal Declaration of Human Rights into the local Pintupi-Luritja vernacular and observing various Indigenous interactions with law enforcement and domestic violence outreach programs, Holcombe offers new insights into our understanding of how the global rights discourse is circulated and understood within Indigenous cultures. She reveals how, in the postcolonial Australian context, human rights are double-edged: they enforce assimilation to a neoliberal social order at the same time that they empower and enfranchise the Indigenous citizen as a political actor. Remote Freedoms writes Australia's Indigenous peoples into the international debate on localizing rights in multicultural terms.